THE ROLE OF RICE BRAN LIPASE ENZYME AS A CATALYST IN THE FORMATION OF MONOGLYCERIDES BY GLYCEROLYSIS OF PALM KERNEL OIL AND RBD STEARIN - Masyhura MD (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The research to determine the role of lipase of rice bran as a catalyst in the reaction gliserolisis palm kernel oil and RBD Stearin has been carried out. Process glysrolysis was done by mixed glycerol: palm kernel oil: RBD Stearin with a mole ratio 1: 1: 4, 2: 2: 4, 3: 3: 4 and 4: 4: 4. Further results of gliserolisis by determination of monoglyseride content and the highest yield  monoglycerides characterized by FT-IR. The results showed that the enzyme lipase from rice bran can be used as catalysts in the reaction mixture monoglycerides glyserolysis forming compound at a ratio of 2: 2: 4, namely 8.9% and FT-IR analysis shows the presence of OH groups in the wavelength range of 3500 cm‑1.Keywords: rice bran, lipase, catalyst, monoglyseride, palm oil